PARTISIPASI POLITIK KOMUNITAS SAMIN BIDANG PENDIDIKAN - Moh. Rosyid (IAIN Pekalongan, 2009)
In the implementation of education, the government is faced with social reality; communities that respond to formal education - that is active, refuse, and active but not required to receive religious education ‘Pancasila’. This community named Samin Kudus Community, since this society has a local religion that is religion of Adam. It is handed down by the ancestors through oral tradition, without the scriptures and teachings of the transformation process by customary leaders. Each of those three responses have arguments. Actively on formal education due to the principle, whether educated or not educated in formal education, is not a guarantee of the child being good or not good. While refusing formal education because if one conducts formal education, it stimulate the child to be able to read and write, hence the ability will direct the child to be working outside of agriculture. It impacts that the child will work beyond parents’ monitoring and being feared that they will release kinship ties, communication with the general public and aroused a culture that shunned by Samin, for example, the marriage with a person other than followers of Samin. Whilst the latest, actively in formal education but would not be required to receive religious education under the pretext of religion has its own opinion, that they posses their own religion, namely Adam.